Contacts of retreatment tuberculosis cases with a prior poor treatment outcome are at increased risk of latent tuberculosis infection - Davit Baliashvili; Matthew J. Magee; Russell R. Kempker; Giorgi Kuchukhidze; Ana Aslanikashvili; Henry M. Blumberg (International Journal of Infectious Diseases, 2016)
Objectives: To estimate the prevalence of and risk factors for latent tuberculosis infection (LTBI) among contacts of index patients with tuberculosis (TB) with a prior history of active TB disease and TB treatment (retreatment cases). Methods: A cross-sectional population-based study was conducted using data from the national TB contact surveillance program in the country of Georgia. Contacts of retreatment cases were investigated and tuberculin skin testing was offered. Bivariate and multivariable analyses were performed to calculate odds ratios (OR) and 95% confidence intervals for risk of LTBI among contacts. Results: The prevalence of LTBI was significantly higher among contacts whose index TB patient had had a prior unfavorable treatment outcome compared to those who had had a favorable outcome (OR 3.14). Contacts whose index TB case had previously failed therapy (OR 6.43), was lost to follow-up (OR 5.63), or had completed treatment (OR 3.33) had a significantly higher prevalence of LTBI compared to contacts of previously cured TB cases. Conclusions: Among contacts of active TB retreatment cases, the risk of LTBI was related to the outcome of the index case's previous TB treatment. Efforts aimed at reducing treatment loss to follow-up should be emphasized to enhance TB control efforts and may also decrease LTBI and active TB among contacts.